The role of Interleukin -18 / Interleukin -18 BindingProtein in Rheumatoid Arithritis patients - Saleh Al-quraishi, Ghadah Mohommed (Iraqi Journal of Science, 2023)
Rheumatoid arthritis (RA) is a chronic inflammatory polyarithritic diseaseassociated with remission and exacerbation with different immunologicalfeatures.Rheumatoid factor(RF) screening test was used quantitatively and qualitativelyusing an enzyme immunoassay (EIA), RF-isotypes (RF-IgG, RF-IgM, RF-IgA) ,Interleukin-18 (IL-18) and Interleukin – 18 binding protein (IL-18BP) were detectedquantitatively usingenzyme linked immunosorbent assay(ELISA). Results indicated a51% positivity in RF among RA patients and a prevalence of the RF-isotype (RF-IgM)with the highest level at (41.6±16.3 U/ml) (p < 0.05) among other RF-isotypes at apercentage of 85.5% , results also indicatedan elevated serum level of IL-18 and IL-18BP(225±24.8 pg/ml), ( 5.2 ± 2.1 ng/ml ) respectively compared to healthy control(HC)group (65±8.4 pg/ml )(p<0.01) , ( 2.9 ± 1.3 ng/ml ) (p<0.05) respectively, andratio of IL-18/IL-18BP serum levels in RA patients were significantly higher than in HCgroup (p<0.05) which increased the importance of IL-18BP in therapeutic strategy. Inconclusion RF-IgM may be an important complimentary detection method for RAamong the other isotypes ,IL-18 with its IL-18BP may play an important role in RAwhich need to be further investigated.